1986
DOI: 10.1007/bf03259830
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Iron Poisoning

Abstract: Acute iron poisoning is most common in children below the age of 5 years. While there is no doubt that it may be fatal, recent surveys show that death occurs in only a very small percentage of cases and that iron salts are responsible for a small minority of fatalities due to overdosage with drugs. Similarly, the proportion of severe cases seems to have fallen over the last thirty years, possibly due to earlier and more aggressive treatment but more probably due to an increase in the number of minor exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 73 publications
0
14
0
2
Order By: Relevance
“…3 ' 4 ' [9][10][11][12] More recently, others have indicated that the TIBC is not measured consistently in acute overdose situations by certain methods, one using magnesium carbonate and the other using an iron-absorbing resin, and, therefore, should not be relied on. 67 It remains to be determined whether appropriate measurement of the TIBC can facilitate correct medical decisions about chelation.…”
Section: -5mentioning
confidence: 99%
“…3 ' 4 ' [9][10][11][12] More recently, others have indicated that the TIBC is not measured consistently in acute overdose situations by certain methods, one using magnesium carbonate and the other using an iron-absorbing resin, and, therefore, should not be relied on. 67 It remains to be determined whether appropriate measurement of the TIBC can facilitate correct medical decisions about chelation.…”
Section: -5mentioning
confidence: 99%
“…Features of acute gastrointestinal irritation dominate the period up to 6 h after ingestion, and most patients do not develop other features or progress beyond this stage. Hypotension may arise at this stage either due to hypovolaemia or due to blood loss 2 3 7. In the index case, it was probably due to hypovolaemia.…”
Section: Discussionmentioning
confidence: 96%
“…Acute kidney injury and hepatocellular failure may develop in a few patients during this stage. The last (fourth) phase, which usually develops in young children 2–6 weeks after ingestion, is characterised by the recurrence of vomiting due to gastric or duodenal stenosis caused by the healing of gastric erosions 2 3 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…therapy for acute iron intoxication, we have had preliminary evidence that diazepam may reduce mortality following the administration of a lethal dose of iron. To date all attempts at decreasing morbidity and mortality from acute iron overdose have focused on gut decontamination and systemic chelation of the metal (Tenenbein 1985;Proudfoot et al 1986). The benzodiazepines have never been either proposed or tested in this condition, as there was no theoretical or hypothetical framework to rationalize such an experiment.…”
Section: Microscopic Tissue Analysismentioning
confidence: 99%